mtDNA in the Pathogenesis of Cardiovascular Diseases - Lili Wang (Hindawi Limited, 2021)
The incidence rate of cardiovascular disease (CVD) has been increasing year by year and has become the main cause for the increase of mortality. Mitochondrial DNA (mtDNA) plays a crucial role in the pathogenesis of CVD, especially in heart failure and ischemic heart diseases. With the deepening of research, more and more evidence showed that mtDNA is related to the occurrence and development of CVD. Current studies mainly focus on how mtDNA copy number, an indirect biomarker of mitochondrial function, contributes to CVD and its underlying mechanisms including mtDNA autophagy, the effect of mtDNA on cardiac inflammation, and related metabolic functions. However, no relevant studies have been conducted yet. In this paper, we combed the current research status of the mechanism related to the influence of mtDNA on the occurrence, development, and prognosis of CVD, so as to find whether these mechanisms have something in common, or is there a correlation between each mechanism for the development of CVD?